Mitochondrial RNA editing in Trypanoplasma borreli: New tools, new revelations - Gerasimov, Evgeny S; Afonin, Dmitry A; Korzhavina, Oksana A; Lukeš, Julius; Low, Ross; Hall, Neil; Tyler, Kevin; Yurchenko, Vyacheslav; Zimmer, Sara L (Computational and structural biotechnology journal, 2022)
The kinetoplastids are unicellular flagellates that derive their name from the 'kinetoplast', a region within their single mitochondrion harboring its organellar genome of high DNA content, called kinetoplast (k) DNA. Some protein products of this mitochondrial genome are encoded as cryptogenes; their transcripts require editing to generate an open reading frame. This happens through RNA editing, whereby small regulatory guide (g)RNAs direct the proper insertion and deletion of one or more uridines at each editing site within specific transcript regions. An accurate perspective of the kDNA expansion and evolution of their unique uridine insertion/deletion editing across kinetoplastids has been difficult to achieve. Here, we resolved the kDNA structure and editing patterns in the early-branching kinetoplastid Trypanoplasma borreli and compare them with those of the well-studied trypanosomatids. We find that its kDNA consists of circular molecules of about 42 kb that harbor the rRNA and protein-coding genes, and 17 different contigs of approximately 70 kb carrying an average of 23 putative gRNA loci per contig. These contigs may be linear molecules, as they contain repetitive termini. Our analysis uncovered a putative gRNA population with unique length and sequence parameters that is massive relative to the editing needs of this parasite. We validated or determined the sequence identity of four edited mRNAs, including one coding for ATP synthase 6 that was previously thought to be missing. We utilized computational methods to show that the T. borreli transcriptome includes a substantial number of transcripts with inconsistent editing patterns, apparently products of non-canonical editing. This species utilizes the most extensive uridine deletion compared to other studied kinetoplastids to enforce amino acid conservation of cryptogene products, although insertions still remain more frequent. Finally, in three tested mitochondrial transcriptomes of kinetoplastids, uridine deletions are more common in the raw mitochondrial reads than aligned to the fully edited, translationally competent mRNAs. We conclude that the organization of kDNA across known kinetoplastids represents variations on partitioned coding and repetitive regions of circular molecules encoding mRNAs and rRNAs, while gRNA loci are positioned on a highly unstable population of molecules that differ in relative abundance across strains. Likewise, while all kinetoplastids possess conserved machinery performing RNA editing of the uridine insertion/deletion type, its output parameters are species-specific.
Keywords: Euglenozoa; Mitochondrion; ATPase 6; Maxicircle; RNA editing; U-indel editing, Uridine insertion/deletion editing; guide RNA; Metakinetoplastina